2006
DOI: 10.1300/j233v05n01_06
|View full text |Cite
|
Sign up to set email alerts
|

Drug Abuse, Risks of Infectious Diseases and Service Utilization Among Former Soviet Union Immigrants

Abstract: Based on the high rates of injection drug use and infectious disease such as HIV, HCV and tuberculosis in their home country, immigrants from the Former Soviet Union (FSU) comprise a high-risk population in the United States. Yet, little is known about their drug abuse and health problems relative to other immigrant populations like Hispanics. The objectives of this exploratory study were to identify disease risk behavior, and utilization of and barriers to treatment services among drug using immigrants from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 3 publications
2
18
3
Order By: Relevance
“…Data from these studies also suggest that young FSU immigrant injectors engage in a range of drug-use practices that place them at elevated risk for exposure to HIV and HCV, 2,3 including injecting drugs in group settings, sharing injection equipment and drug solution, and use of public injection spaces. 9,10 Although large-scale HIV or HCV prevalence data for U.S.-based FSU immigrants are unavailable, a community screening study found a background HCV prevalence of 28.3% 11 in NYC’s general FSU-born population – a rate that far exceeds that of the U.S. population (1.3% 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from these studies also suggest that young FSU immigrant injectors engage in a range of drug-use practices that place them at elevated risk for exposure to HIV and HCV, 2,3 including injecting drugs in group settings, sharing injection equipment and drug solution, and use of public injection spaces. 9,10 Although large-scale HIV or HCV prevalence data for U.S.-based FSU immigrants are unavailable, a community screening study found a background HCV prevalence of 28.3% 11 in NYC’s general FSU-born population – a rate that far exceeds that of the U.S. population (1.3% 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only two small, qualitative research studies have focused on substance use within FSU immigrant communities in the U.S. 2,3 These reports, along with a handful of more general studies of drug use in NYC, indicate that heroin use and IDU began to be recognized as growing problems for young people in NYC’s Russian-speaking communities in the mid-late 1990’s, during the largest wave of immigration from the FSU to the U.S. 4,5,6,7 Clinical evidence from NYC drug treatment providers confirms that a marked propensity for heroin injection (often used in tandem with cocaine and other drugs) has tended to distinguish FSU immigrant youth from other groups of young people in drug treatment for the past 15–20 years. 8 During the earlier years of this period, some (albeit a minority of) FSU immigrants entering drug treatment had initiated opioid use in the high-risk drug-use environment of the FSU, characterized by widespread syringe-sharing and hyper-endemic HIV and hepatitis C virus (HCV), while in more recent years, this is increasingly rare, as most FSU immigrants who are young adults today immigrated to the U.S. in childhood or early adolescence and initiated drug use in the U.S. 2 …”
Section: Introductionmentioning
confidence: 99%
“…Although we could only distinguish between Eastern European and non-Eastern European immigrants, we believe that our results are informative because IDUs from the Eastern European countries represent a high proportion of the immigrants recruited in harm reduction centers. It is important to consider the Eastern European Immigrants separately, because they are a high risk group to become users of injected drugs (Isralowitz, Straussner, & Rosenblum, 2006) due to the specific behaviours they have (Freixa & Meroño, 2011). Differences in illegal drug consumption between native and immigrants in a large sample of injected drug users in Catalonia (Spain)…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Although national data on the prevalence of substance use among FSU-born or Russian-speaking immigrants living in the U.S. are not available, recent evidence from NYC suggests that substantial numbers of young FSU immigrants are engaging in opioid and injection drug use (IDU) (Guarino, Marsch, Deren, Straussner, & Teper, 2015; Guarino, Moore, Marsch, & Florio, 2012; Isralowitz, Straussner, & Rosenblum, 2006). Emerging research has documented concerning patterns of drug use and related risk behaviour within NYC’s Russian-speaking community that resemble trends seen in many other communities across the country; these include early initiation of nonmedical prescription opioid (PO) use, frequent progression to heroin use and IDU, high rates of injection-related risk behaviour within peer networks, and associated increases in hepatitis C virus (HCV) incidence among youth under 30 (Guarino et al, 2015, 2012; Prussing, Bornschlegel, & Balter, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Not only does this deeply entrenched, dehumanising ideology towards drug users ramify throughout the former Soviet region, it also extends to the Russian-speaking diaspora, influencing the attitudes and behaviours of FSU immigrants, particularly members of older generations who came of age in the Soviet era and emigrated in adulthood (Isralowitz et al, 2006; Kagan & Shafer, 2001). Research on drug users in former Soviet countries has found that fear of stigmatisation from family members and the wider society deters them from seeking drug treatment and disease prevention services or even being seen in the vicinity of “narcology” (the Soviet model of drug treatment) centres (Spicer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%